Michael J. Fabricant and Robert Fisher (2002): Settlement Houses Under Siege: The Struggle to Sustain Community Organisations in New York City. New York: Columbia University Press, pp. 360 pages. - Norma Baldwin (Social Work & Society, 2003)
This is a fascinating book - clear, incisive, a lesson for our times. It focuses on the history and recent experience of Settlement Houses in New York and uses this as a vehicle for an analysis of the political economy of welfare agencies. I wanted to send copies to politicians and policy makers worldwide who, whilst claiming to support social inclusion, community regeneration and equal opportunities, formulate policies that fragment societies and oppress poor and vulnerable people.